Dynamical system of flat electroencephalography - Ken, Tan Lit (Science Publications, 2015)
Flat EEG is a way of viewing electroencephalography signals on the real plane. The wealth of information contained within makes it a great platform to study epileptic seizure. In this study, the time embedment nature of Flat EEG is exploited to establish a dynamic Flat EEG model. Basically, a geometrical representation which displays the important information visually for Flat EEG at any time will firstly be formulated, followed by the representation of a Flat EEG signal as a trajectory in state space. Based on these, the modeling of Flat EEG as a dynamical system using the notion of flow is presented. This dynamic model would serve as the groundwork for the indisputably essential dynamic justification of Flat EEG in future research.